2020
DOI: 10.1002/pc.25821
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbon nanotube type and novel modification on dispersion, melt‐rheology and electrical conductivity of polypropylene/carbon nanotube composites

Abstract: Melt‐mixing was employed to prepare multiwall carbon nanotubes (MWCNTs) based polypropylene (PP) composites, wherein MWCNTs vary in “agglomerate” size and also in terms of “agglomerate” structure. Morphological analysis revealed MWCNTs‐D type exhibits bigger “agglomerate” size with compact “agglomerate” structure with respect to MWCNTs‐N type, that show smaller “agglomerate” size with porous “agglomerate” structure in the corresponding PP/MWCNTs composites. Melt‐rheological analysis showed a rheological percol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…[6][7][8] To relinquish the gap between the polymer composite services to the requirements of the application, utilization of nanoparticles for developing polymer nanocomposites is now being set forward. [9] Polymer nanocomposites are the composites produced by the combination of polymer matrix with the dispersion of nanoparticles. [10] It has been found that the inclusion of nanoparticles enhances various properties of polymer composite, such as superior toughness and mechanical strength, excellent electrical and thermal properties, outstanding flame retardancy, and a more significant barrier to moisture and gases.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] To relinquish the gap between the polymer composite services to the requirements of the application, utilization of nanoparticles for developing polymer nanocomposites is now being set forward. [9] Polymer nanocomposites are the composites produced by the combination of polymer matrix with the dispersion of nanoparticles. [10] It has been found that the inclusion of nanoparticles enhances various properties of polymer composite, such as superior toughness and mechanical strength, excellent electrical and thermal properties, outstanding flame retardancy, and a more significant barrier to moisture and gases.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier we have observed a higher average agglomerate size corresponding to D‐MWCNTs as compared to N‐MWCNTs from optical microscopic analysis. [ 24 ] The higher L/D ratio (~270 for D‐MWCNTs as compared to ~158 for N‐MWCNTs) [ 14 ] leads to higher extent of agglomeration in D‐MWCNTs. Further, N‐MWCNTs show higher value of specific surface area as compared to D‐MWCNTs due to less compact agglomerate structure associated with N‐MWCNTs, which involve higher fraction of individualized nanotubes.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in temperature corresponds to T onset and T final values in PP/MWCNTs is due to the kinetic barrier imposed by nanotubes, which delays the degradation process of PP. Further, as the concentration of the nanotubes exceeds the electrical percolation threshold, [ 14 ] the action of MWCNTs on delaying the thermal degradation of PP is much more evident from the respective T onset and T final corresponding to PP/MWCNTs composites. Moreover, these values along with residual weight data also suggest that PP chains engage in interfacial interaction with “individualized” MWCNT, thus forming a thicker “interphase.” The influence of N‐MWCNTs is higher as compared to D‐MWCNTs in the formation of thicker “interphase,” which is due to the presence of higher fraction of “individualized” N‐MWCNTs in the respective composites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations